2005
DOI: 10.1111/j.1399-0039.2005.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Association study of Toll‐like receptor 9 gene polymorphism in Korean patients with systemic lupus erythematosus

Abstract: Mammalian Toll-like receptors (TLR) play an important role in both adaptive immunity and innate immunity. Genetic variations within TLR genes are known to be associated with a variety of inflammatory and infectious diseases. TLR9 is potentially associated with autoimmune diseases, because it participates in the production of pro-inflammatory cytokines and the maturation of dendritic cells. We investigated the association of four TLR9 gene polymorphisms (-1486 T>C, -1237 C>T, +1174 A>G and +2848 G>A) with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
3
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 19 publications
5
33
3
4
Order By: Relevance
“…One can imagine that genetic variation affecting TLR-9 function could affect the threshold for B cell or dendritic cell activation. We have extended the initial findings from the study by Hur and colleagues (6), who reported no association with SLE in 4 polymorphisms found in a 4,334-bp segment of DNA in the vicinity of TLR-9. Our study examined a much (Figure 1).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…One can imagine that genetic variation affecting TLR-9 function could affect the threshold for B cell or dendritic cell activation. We have extended the initial findings from the study by Hur and colleagues (6), who reported no association with SLE in 4 polymorphisms found in a 4,334-bp segment of DNA in the vicinity of TLR-9. Our study examined a much (Figure 1).…”
Section: Discussionsupporting
confidence: 68%
“…In surveying this genomic segment, we found no evidence of association with SLE for the 9 polymorphisms and 8 haplotypes tested. Two of the tested SNPs (rs352140 and rs187084) were genotyped in a Korean population (6) in addition to the present UK population, and both were found to have similar allele frequencies in the 2 populations. Results of the 2 studies can therefore be compared directly at these points and are consistent in showing no evidence of association with SLE.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Извест-но, что такие полиморфизмы (single nucleotide polymorphisms) гена TLR2, как Arg753Gln, T597C ассоциированы с инфекцией, вызванной Candida albicans, M. tuberculosis, цитомегалови-русом, вирусом герпеса простого 2 типа и други-ми патогенами [9,16,17]. Полиморфизмы гена TLR9 G1174A, G1635A, A2848G ассоциированы с системной красной волчанкой, развитием ин-фекции, вызванной HIV-1 и другими заболе-ваниями [5,7]. Вышеперечисленные полимор-физмы располагаются как в LRR-домене TLRs, распознающем патоген, так и в TIR-домене, Полиморфизм TLR при инфекции 2010, Т.…”
Section: ганковская оа медицинская иммунологияunclassified
“…One study in Korean patients showed that TLR9 gene polymorphisms were not significantly associated with susceptibility to SLE and related phenotypes [35]. It is likely that other TLRs (TLR7, TLR3?)…”
Section: The External World-infections and Autoantigens (Molecular MImentioning
confidence: 99%